2022
DOI: 10.1001/jamapediatrics.2022.0494
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Parental Cancer With School Absenteeism, Medical Care Unaffordability, Health Care Use, and Mental Health Among Children

Abstract: IMPORTANCE A cancer diagnosis can adversely affect other members of the family, including children. However, little is known about the extent to which history of parental cancer affects children's health.OBJECTIVE To examine associations of parental cancer with children's school absenteeism, medical care unaffordability, health care use, and mental health. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional, nationally representative study used data from the 2010-2018 National Health Interview Survey. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…Moreover, non-Hispanic Black children, children whose parents had poor health, and children living in low-income families were more likely to experience food insecurity and parent’s financial worry about paying monthly bills and housing costs. Our findings add to the accumulating evidence that a cancer diagnosis can adversely affect physical and mental health and financial burden for other family members, including spouses and other informal caregivers . Our findings also suggest that efforts to identify children with a parental cancer history and screen for any unmet economic needs and connect them with relevant services are warranted.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Moreover, non-Hispanic Black children, children whose parents had poor health, and children living in low-income families were more likely to experience food insecurity and parent’s financial worry about paying monthly bills and housing costs. Our findings add to the accumulating evidence that a cancer diagnosis can adversely affect physical and mental health and financial burden for other family members, including spouses and other informal caregivers . Our findings also suggest that efforts to identify children with a parental cancer history and screen for any unmet economic needs and connect them with relevant services are warranted.…”
Section: Discussionsupporting
confidence: 56%
“…Our findings add to the accumulating evidence that a cancer diagnosis can adversely affect physical and mental health and financial burden for other family members, including spouses and other informal caregivers. [14][15][16][17] Our findings also suggest that efforts to identify children with a parental cancer history and screen for any unmet economic needs and connect them with relevant services are warranted.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Drawing on data from the 2010 to 2018 National Health Interview Survey, they found that when parents of minors experience cancer, children were more likely to miss school, miss well-child checkups, visit emergency departments, and experience negative mental health consequences. 11 In part, these findings make intuitive sense. Witnessing firsthand a loved one experience a life-threatening illness and potentially watching them suffer is inherently upsetting, stressful, even personally threatening.…”
mentioning
confidence: 91%
“…In this issue, Zheng and colleagues further our knowledge about this problem, spelling out this disruption in greater detail. Drawing on data from the 2010 to 2018 National Health Interview Survey, they found that when parents of minors experience cancer, children were more likely to miss school, miss well-child checkups, visit emergency departments, and experience negative mental health consequences …”
mentioning
confidence: 98%